2014
DOI: 10.3109/15513815.2014.949934
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Fetal MRI in the Diagnosis of Type IV Cystic Sacrococcygeal Teratoma-A Review

Abstract: The introduction of fetal magnetic resonance imaging (MRI) has improved the prenatal evaluation of uterine, placental and fetal anatomy. However, its utilization has mostly been restricted to fetal central nervous system anomalies. We review how adjunct fetal MRI was performed and diagnosis of cystic type IV sacrococcygeal teratoma was made. We also discuss the clinical relevance of fetal MRI in differentiating this lesion from other selected abdominal/pelvic cystic malformations and lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
13
0
1
Order By: Relevance
“…One of our patients was diagnosed in prenatal period through an obstetric ultrasound. This diagnosis in the neonatal period allowed an early management by intrauterine or neonatal surgery [2,3,5]. The second circumstance of discovery is an emergency delivery of a newborn with sacrococcygeal mass.…”
Section: Case Report Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…One of our patients was diagnosed in prenatal period through an obstetric ultrasound. This diagnosis in the neonatal period allowed an early management by intrauterine or neonatal surgery [2,3,5]. The second circumstance of discovery is an emergency delivery of a newborn with sacrococcygeal mass.…”
Section: Case Report Discussionmentioning
confidence: 95%
“…The sacrococcygeal teratomas are multi-tissue tumors composed of varying proportions in tissues from all three germ layers (endoderm, ectoderm, and mesoderm) [6]. Their frequency of occurrence varies from 1 in 28,500 to 40,000 births and is found more frequently in the female subject with a sex ratio of 1/3 to 1/4 [1,2,3,7,5]. This epidemiological parameter was verified in our study where both cases were reported in female subjects.…”
Section: Case Report Discussionmentioning
confidence: 99%
See 3 more Smart Citations